A REPORT OF THREE DENTAL IMPLANT FRACTURE AND LITERATURE REVIEW - Rohanian, Ahmad; Taher, Abbas; Shawki, Ammar Albujeer; Pirmoazzen, Salma (European Scientific Journal, ESJ, 2015)
Implant fracture is one of the rare complications in Implant Dentistry. Such fractures pose important problems to both the patient and the dental surgeon. According to most literature sources, the prevalence of dental implant fractures is very low (approximately 2 fractures per 1000 implants in the mouth). However, considering that implant placement is becoming increasingly popular, an increase in the number of failures due to late fractures is to be expected. Clearly, careful treatment can contribute to reducing the incidence of fracture. An early diagnosis of the signs alerting to implant fatigue, such as loosening, torsion or fracture of the post screws and prosthetic ceramic fracture, can help prevent an undesirable outcome. Also, it is important to know and apply the measures required to prevent implant fracture. Therefore, the present literature reported three cases with fractured implants. It also discusses the management options and the possible causal mechanisms underlying such failures. In addition, the factors believed to contribute to implant fracture with literatures review were also discussed.